1989
DOI: 10.1002/tera.1420400606
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock affects cell cycling in the neural plate of cultured rat embryos: A flow cytometric study

Abstract: The effects of heat shock on cell cycling in the mammalian neuroectoderm were determined by applying heat shocks to cultured rat embryos at the neural plate stage, as part of a study on the teratogenic effects of heat shock on neural development. The heat shocks had been characterized previously (Walsh et al.: Teratology 36:181-191, 1987) with respect to their effects on the gross morphological development of the rat embryos. The effects on cell cycling were observed in DNA histograms of neural plate cells rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…This was also the finding by other labs that heat shocked embryos in culture (Mirkes, 1985;Walsh et al, 1987). As observed in vivo, these effects were time-and temperature-dependent (Walsh and Morris, 1989;Breen et al, 1999). Therefore, the cell death that was observed was the predominate effect of heat in embryos in vitro and in vivo.…”
Section: Mechanistic Observationssupporting
confidence: 81%
“…This was also the finding by other labs that heat shocked embryos in culture (Mirkes, 1985;Walsh et al, 1987). As observed in vivo, these effects were time-and temperature-dependent (Walsh and Morris, 1989;Breen et al, 1999). Therefore, the cell death that was observed was the predominate effect of heat in embryos in vitro and in vivo.…”
Section: Mechanistic Observationssupporting
confidence: 81%
“…After heat shock, DNA synthesis has been shown to be reduced. In mammalian cells a short heat shock is sufficient to arrest cell division at S phase (37). It (38), one of which is in the region of the histone genes (region 39D).…”
Section: Discussionmentioning
confidence: 99%
“…This exposure in vivo causes microphthalmia in 100% of surviving embryos [9]. In their flow cytometry studies, Walsh and Morris [85] also found that the heat stressed neurectodermal cells caused a partial synchronisation of the generation cycle by causing cells to accumulate for 1-2 h at the G1-S boundaries after treatments of 42, 43 or 42/43°C. Following treatments of 42 or 42/43°C there was also a barrier to cell progression at the S-G2 boundary.…”
Section: Apoptosis Following Heat Shockmentioning
confidence: 97%
“…However, in some cases, cell division is tightly controlled even though cells adopt fates independently of their lineage history. Using flow cytometry, Walsh and Morris [85] and Walsh et al [74] studied cell cycle changes and regulation and expression levels of hsp27, 71, 73 and 90 mRNA at various stages of the neurectodermal cell generation cycle and the effects of the various heat shock regimes ( fig. 3).…”
Section: Reviewsmentioning
confidence: 99%